Analysis of Students' Relational Understanding Ability Through the Application of Blended Learning Method - Tsa Litsa Rasyid; Karunia Eka Lestari (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
The students' relational understanding by applying blended learning is described in this study. The research method is descriptive quantitative that was performed by pre-experimental with a one-shot case study design. This study involves 33 class VIII students in one of the Karawang State Junior High Schools, which was selected by purposive sampling. There are five questions on the post-test that use as instrument tests. The quantitative data analysis is based on the statistical descriptive and statistical tests. The results show that students who have a high category are six students (18%), the medium category is 25 students (76%), and the low category is two students (6%). The average of all students in the sample class is 61.36, still below the KKM=76. The median test obtained 0,149 â‰¥ 0,025, such that it is rejected or accepted. It suggests that at the 95% confidence interval, the median student's relational understanding ability after applying the blended learning method could not reach the KKM.